PEMIDANAAN TERHADAP KORBAN PENYALAHGUNAAN NARKOTIKA SEBAGAI UPAYA PENCEGAHAN DAN PENANGGULANGAN NARKOTIKA DI KABUPATEN GORONTALO - Attas, Nasrah Hasmiati (Institut Agama Islam Negeri Bone, 2022)
This study aims to (1) To find out how the implementation of punishment for victims of narcotics abuse in Gorontalo Regency. (2) To find out the effectiveness of criminal punishment for narcotics abuse in narcotics prevention in Gorontalo Regency.This research uses descriptive research with an empirical juridical approach. The research method used was a method using primary and secondary data with data collection techniques namely interviews and literature from various libraries. The population of this research is all Bawaslu employees and the community. The sample in this study were 10 people using purposive sampling technique.The results of this study indicate that: 1.) Narcotics in Gorontalo Regency are narcotics users who are caught red-handed using narcotics, will be put into police cells or state detention centers (detention centers). Then the police will develop an investigation process, during the process, victims of narcotics abuse remain in the detention cell. If corroboration of evidence has been found, the Examination Document (BAP) will be sent to the prosecutor. The Prosecutors' Office will form a public prosecutor who will produce an indictment, and then submit it to the district court. When the indictment arrived at the head of the court, a panel of judges was formed to summon the defendant. The case will be tried in the Limboto District Court, if the case has been dismissed in the form of a prison sentence, then the convict will undergo the process of punishment in a prison. 2.) Criminalization of narcotics abuse in narcotics prevention in Gorontalo District is very ineffective because in detention there is no treatment or treatment for narcotics users, other than that the place provided in the penitentiary does not support healing for prisoners who have become addicted to narcotics.